Digital Learning Modules: Perspectives On Usability, Content Quality, And Effectiveness - Utami, Rima Agustia; Ernawati; Nelmira, Weni; Hafidza , Hikmah (UNDIKMA, 2025)
The rapid advancement of science and technology has driven innovation in education, particularly in the development of digital learning modules. This study aimed to evaluate a digital learning module based on three key aspects: usability, content quality, and effectiveness. A descriptive quantitative approach supported by qualitative analysis was employed, involving 59 undergraduate students in the Family Welfare Education program at Universitas Negeri Padang who had used the module for at least three learning topics. Data were collected using a Likert-scale questionnaire and complemented by student interviews. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic analysis. The finfings revealed that the overall evaluation of the module was categorized as “very good” and average score of 4.78 across all aspects. Specifically, usability scored 4.70, content quality 4.82, and affectiveness 4.80. interactive feature such as Quizizz and Kahoot received the highest ratings, while multimedia integration (Youtube videos, images, and audio) effectively enchanced comprehansion. Despite ist overall sucsess, certain features, such as bookmarks, were underutilized. In conclution, the digital learning module was found to be user-friendly, of high quality, and effective in suporting both independent and collaborative learning, making it promising instructional medium for higher education.